AKUNTABILITAS PELAYANAN PUBLIK DALAM PENYELENGGARAAN PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) (Studi Kasus: Badan Pelayanan Perijinan Terpadu Satu Pintu dan Penanaman Modal dan Dinas Tata Ruang dan Perumahan Kota Denpasar) - Sari Dewi, I Gusti Agung Ayu Kartika (CITIZEN CHARTER, 2014)
ABSTRACT Accountability is one of many indicators in good governance. Government Institutions that implement public accountability means that institutions always be responsible for their activities in public. In the reality, most of public administration in Indonesia still having problem in the system of government that have not been effective and efficient. The problem that may come is the difficulty of dealing with constructure permission that make many people who want to construct the buildings break the existing rules. this research will examine the public service accountability in Licensing Service Agency One Stop Investment coordinated with Department of Housing and Spatial Planning in Denpasar by using descriptive qualitative research method. The results of this study indicate that the Denpasar Government has not accountable in providing services for users of those services, can be seen from the interests of the service user is not yet a major priority of public officials. Therefore the government need to increase transparency and accountability in providing services, especially in how long the proccess of the services that complained by service user take time. Keywords: Apparatus, Goverment, Service